2020
DOI: 10.1186/s12886-020-01530-w
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical properties in myopic eyes evaluated via Scheimpflug imaging

Abstract: Background: To investigate the biomechanical properties of the cornea in myopic eyes using corneal visualization Scheimpflug technology (Corvis ST). The relationships between the biomechanical properties of the cornea and the degree of myopia were also investigated. Methods: 265 eyes of 265 subjects were included. Based on spherical equivalent (SE) in diopters (D), participants were divided into four groups: low myopia/control (SE: − 0.50 to − 3.00D), moderate myopia (SE: − 3.00 to − 6.00D), high myopia (SE: −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Consistent with our results, Matalia et al [22] also showed that corneal deformation parameters were unaffected by myopia. However, some other studies [23,24] found that the cornea became more deformable with elongation of the AL with corresponding increases in myopia. The effect of age and AL with DCRs needs to be further verified.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with our results, Matalia et al [22] also showed that corneal deformation parameters were unaffected by myopia. However, some other studies [23,24] found that the cornea became more deformable with elongation of the AL with corresponding increases in myopia. The effect of age and AL with DCRs needs to be further verified.…”
Section: Discussionmentioning
confidence: 90%
“…This may cause excessive stretching of the retina, choroid, and sclera, which in turn result in a series of eye complications such as macular degeneration, retinal detachment, and posterior staphyloma ( Ohno-Matsui and Jonas, 2019 ). In recent years, researchers have investigated the relationship between corneal biomechanics and axial elongation, and have arrived at various conclusions ( Hon et al, 2017 ; Matalia et al, 2017 ; Long et al, 2019 ; Tubtimthong et al, 2020 ; Yu et al, 2020 ). Long et al believed that spherical equivalent refraction was significantly positively correlated with the stiffness parameter at the first applanation (SP-A1) ( Long et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that high myopia can cause corneal biomechanical changes ( Moshirfar et al, 2019 ). Some studies found a negative correlation between corneal biomechanics and AL ( Long et al, 2019 ; Tubtimthong et al, 2020 ; Yu et al, 2020 ) and suggested that measuring corneal biomechanics can predict axial elongation ( Haseltine et al, 2012 ; Zadnik et al, 2015 ; Long et al, 2019 ; Wu et al, 2019 ). In contrast, other studies suggested that corneal biomechanics is independent of the severity of refractive error ( Lim et al, 2008 ; Inceoglu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of myopia is believed to be induced by various patterns of ocular expansions, including equatorial expansion [5], axial expansion [6], and posterior pole expansion [7]. Accompanied by these expansions, the pathogene-sis of myopia includes the biomechanical alternations of the eyeball outer wall, including the cornea, scleral, lamina cribrosa, and peripapillary ring [8,9]. The corneal stiffness was reported to be reduced with the increase in the myopic degree from Corneal Visualization Scheimpflug Technology (Corvis ST, Oculus, Wetzlar, Germany) studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%